2022
DOI: 10.1155/2022/2454180
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value, Medicinal Importance, and Health-Promoting Effects of Dietary Mushroom (Pleurotus ostreatus)

Abstract: Pleurotus ostreatus is the second cultivated and most popular edible mushroom after Agaricus bisporus worldwide. As dietary supplements, nutraceuticals like Pleurotus ostreatus that go beyond the usual health benefits of mushrooms are becoming more popular. The objective of this study is to put together a summary of the nutrition information and link it to the possible health benefits and health-improving effects of eating oyster mushrooms. This review is based on secondary data from 102 published articles abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 61 publications
(77 reference statements)
2
23
0
1
Order By: Relevance
“…In addition, mushrooms contain the following mineral elements: K, P, Na, Ca, Mg, Cu, Zn, Fe, Mo, and Cd. They are rich in B vitamins (thiamine, riboflavin, pyridoxine, pantothenic acid, nicotinic acid, nicotinamide, folic acid, and cobalamin), vitamins C, and vitamin D2 [12,13]. The fruit bodies of Pleurotus ostreatus are characterized by a high content of phenolic substances, beta-glucans, ergothioneine, lectin, glycopeptides, proteoglycans, and lovastatin [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mushrooms contain the following mineral elements: K, P, Na, Ca, Mg, Cu, Zn, Fe, Mo, and Cd. They are rich in B vitamins (thiamine, riboflavin, pyridoxine, pantothenic acid, nicotinic acid, nicotinamide, folic acid, and cobalamin), vitamins C, and vitamin D2 [12,13]. The fruit bodies of Pleurotus ostreatus are characterized by a high content of phenolic substances, beta-glucans, ergothioneine, lectin, glycopeptides, proteoglycans, and lovastatin [12].…”
Section: Introductionmentioning
confidence: 99%
“…They are rich in B vitamins (thiamine, riboflavin, pyridoxine, pantothenic acid, nicotinic acid, nicotinamide, folic acid, and cobalamin), vitamins C, and vitamin D2 [12,13]. The fruit bodies of Pleurotus ostreatus are characterized by a high content of phenolic substances, beta-glucans, ergothioneine, lectin, glycopeptides, proteoglycans, and lovastatin [12]. These biologically active metabolites have antioxidant [14,15], anti-inflammatory [16,17], antihyperlipidemic [18], and antidiabetic [19,20] effects.…”
Section: Introductionmentioning
confidence: 99%
“…The 1D NMR spectroscopic data (Table 1) of 2 indicated the presence of two sp 2 nonprotonated carbons (δ C 132.0 and 135.4), three sp 3 nonprotonated carbons including two oxygenated (δ C 75.7 and 74.8), two sp 2 methines (δ C 125.8 and 126.8), three sp 3 methines including two oxygenated (δ C 81.2 and 79.0), eight sp 3 methylenes, and seven methyls, which are similar to those of compound 1. Comparison of 1D NMR spectra revealed that compound 2 possesses two more signals for sp 3 The NOESY correlation from H-14 to H 2 -16 suggested a trans configuration of the double bond at C-14 (Figure 6). The absolute configurations of the 10-OH and 18-OH of 2 were speculated to be the same as those of PA according to the same biogenetic origin, that is, 10S and 18S.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1,2 Pleurotus ostreatus, the second most commonly cultivated mushroom after Agaricus bisporus globally, can be easily cultivated, exhibits rapid growth, and possesses a great value in nutrition and medical application. 3,4 The mycelium of P. ostreatus can be cultivated by submerged fermentation, which has the advantages of a short fermentation period, stable product spectrum, and easy industrial scale-up; it is therefore suitable for the research of medicinal substances and the relevant biosynthetic gene clusters. However, currently only about 14 terpenoids have been identified in P. ostreatus, 11 of them from liquid hyphae fermentation and three of them from the fruiting body (see Figure S1 in the Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation